Twin Prime Number Theorem (Global Journal of Science Frontier Research, 2017)
Let Pt(N) be the number of twin primes less than or equal to N, Pi (3 Pi Pm) be taken over the odd primes less than or equal to √N, then exists the formula as follows: Pt(N) ≥ INT { N×(1－1/2)×Π (1－2/Pi) } － 2 ≥ INT { Ct×2N/(Ln (N))^2 } － 2 Pt(N) ≥ INT { 0.660×2N/(Ln (N))^2 } － 2 ≥ 0.660×2N/(Ln (N))^2 － 3 Π ( Pi(Pi－2)/(Pi－1)^2 ) ≥ Ct ＝ 0.6601618158… Where the INT { } expresses the taking integer operation of formula spread out type in { }.
Keywords: twin prime; bilateral sieve method